Inovasi e-LKPD berbasis problem based learning berbantuan canva untuk meningkatkan kemampuan berpikir kreatif matematis siswa SMP - Ratnasari Pujianti; Wahyu Hidayat; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Mathematics learning on statistics topics still faced various challenges, such as the use of less interactive teaching materials. This study aimed to develop a Canva-assisted Problem-Based Learning e-LKPD to improve junior high school students' mathematical creative thinking skills. This study employed a Research and Development approach using the ADDIE model. The research subjects were 30 seventh-grade students from a junior high school in West Bandung Regency. Data were collected through mathematical creative thinking skills tests, student response questionnaires, interviews, and expert validation sheets. Data were analyzed using the Normalized Gain (N-Gain) test, normality test, and Wilcoxon test. The results showed that the feasibility level of the developed e-LKPD was categorized as highly feasible based on expert validation, limited trials, and large-scale trials. The N-Gain results indicated that students’ mathematical creative thinking skills improved at a high and effective level. Therefore, the Canva-assisted Problem-Based Learning e-LKPD was feasible and effective for use in statistics learning. This study contributed by providing an alternative digital teaching material that supported the improvement of junior high school students’ mathematical creative thinking skills.